In vitro effects of ascorbic acid on viability and metabolism of patients’ osteosarcoma stem cells - Jovičić Marijana Šimić; Pušić Maja; Antunović Maja; Ledinski Maja; Librenjak Lucija; Kolundžić Robert; Ribičić Tomislav; Trkulja Vladimir; Urlić Inga (Acta Pharmaceutica)
Stagnation in novelties of osteosarcoma (OS) treatment indicates the need for new therapeutic methods. OS cancer stem cells (OS-CSC) are taught to have the ability to self-renew and develop mechanisms of anticancer drug resistance, and this is why it is difficult to eradicate them. Their metabolism has been recognized as a potential target of therapeutic action. Ascorbic acid (AA) is considered to act pro-oxidative against OS-CSC in vitro by oxidative effect and by inhibition of glycolysis. This study examined an in vitro impact of AA on OS-CSC metabolism isolated from patients’ biopsies, with the aim of better understanding of OS-CSC metabolism and the action of AA on OS-CSC. OS-CSC were isolated using a sphere culture system and identified as stem cells using Hoechst 33342 exclusion assay. Determination of the dominant type of metabolism of OS-CSC, parental OS cells, human mesenchymal stem cells (hMSC) and U2OS OS lineage before and after AA treatment was done by Seahorse XF (Agilent). Cytotoxicity of high-dose AA was confirmed by the MTT test and was proven for all the examined cell types as well as HEK293. Seahorse technology showed that OS-CSC can potentially use both glycolysis and oxidative phosphorylation (OXPHOS), and can turn to glycolysis and slow metabolic potential in unfavorable conditions such as incubation in AA.